Entrepreneurial Migration - Bryan, Kevin A.; Guzman, Jorge (The Review of Economics and Statistics, 2026)
We track the movement of high-potential startups using cross-state business registrations and estimate the utility of cities to moving startups using a revealed preference approach. 6.6% of these startups move across state borders during their first five years. Startup hubs like Silicon Valley and Boston tend to lose startups to other cities. Our findings show that startups prefer traditional hubs when they move soon after being founded, but later prefer cities with lower taxes. This pattern is not due to vertical sorting or industrial specialization.